Pengaruh Pendidikan Kesehatan Media Booklet Terhadap Tingkat Pengetahuan Ibu Hamil Tentang Tumbuh Kembang Janin - Nur Hidayatul Ainiyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Mother's knowledge about fetal growth and development is essential for monitoring fetal growth and early detection of growth and development abnormalities from the perceived size and movement of the fetus; this is a form of mother empowerment in pregnancy care. With the knowledge that pregnant women have about the growth and development of the fetus, the mother can observe the growth and development of the fetus from the size of the uterus and the movement of the fetus every day so that pregnant women can make early detection of one of the danger signs of pregnancy.Methods: This study uses a quasi-experimental pre-post test experiment The population in this study were all pregnant women in trimesters 1,2, and 3 with a sample of 54 pregnant women at PMB Surabaya. It was conducted from March until June 2020.Results: From the analysis of the pasted t-test, it is known that there are differences between pre-test and post-test, as the value of p=0.000<0.05.Conclusion: Thus, Ho is rejected, which means that there is an influence of education on fetal growth and development using booklet media on the level of knowledge of pregnant women